2020
DOI: 10.2196/22913
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of a Personal Health Record in the Digital Age: Cross-Sectional Study

Abstract: Background As health care organizations strive to improve health care access, quality, and costs, they have implemented patient-facing eHealth technologies such as personal health records to better engage patients in the management of their health. In the Kingdom of Saudi Arabia, eHealth is also growing in accordance with Vision 2030 and its National Transformation Program framework, creating a roadmap for increased quality and efficiency of the health care system and supporting the goal of patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Although social influences such as interactions with health care providers have been identified as important in patients’ adoption of PHRs, our findings did not find a significant impact [ 7 , 8 , 32 ]. Yousef et al [ 19 ], however, reported that health care providers (47.9%) or hospital staff (10.8%) were mainly responsible for recommending the use of MNGHA Care. Facilitating conditions likely did not have a significant impact as users found the organizational resources and technical help adequate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although social influences such as interactions with health care providers have been identified as important in patients’ adoption of PHRs, our findings did not find a significant impact [ 7 , 8 , 32 ]. Yousef et al [ 19 ], however, reported that health care providers (47.9%) or hospital staff (10.8%) were mainly responsible for recommending the use of MNGHA Care. Facilitating conditions likely did not have a significant impact as users found the organizational resources and technical help adequate.…”
Section: Discussionmentioning
confidence: 99%
“…Data for the study were obtained from a cross-sectional survey study [ 19 ] in which data were collected to examine health information–seeking behavior and PHR (MNG-HA Care) use among patients. Secondary data were used in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Our study found a high level of awareness among HCPs, with 88.2% (217/246) having an account and 82.1% (202/246) recommending patients use the PHR. In our previous study in patients, HCPs and hospital staff were primarily responsible for recommending the PHR in 58.7% of patients who reported using MNGHA Care [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCPs play a key role in supporting and engaging patients through their attitudes, behavior, and endorsement of services [ 17 ]. Although studies have shown a high level of patient interest in PHRs [ 5 , 18 - 20 ], there has been a disconnect between interest and uptake. This is partially due to HCPs’ reticence toward the acceptance and promotion of their use [ 5 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given digital health innovations worldwide, e-platforms supporting conventional and novel pharmacy practice in Saudi Arabia are needed. Saudi consumers too, appear to engage with emerging e-health pathways, e.g., use of electronic health records which have been implemented in some public hospitals in alignment with the Vision 2030 [ 38 ]. Telehealth and digital technology use by community pharmacists has the potential to improve health outcomes [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%